Interoceptive Awareness and Female Orgasm Frequency and Satisfaction - Emily Dixon; Giulia L. Poerio; Gerulf Rieger; Megan Klabunde (Brain Sciences)
Background: The female orgasm is a highly understudied phenomenon that is linked to both wellbeing and relationship satisfaction in women. Although orgasm has been associated with interoception—the sense of the physiological condition of the body—very few studies have directly examined the influence that interoception has on orgasm. Objectives: This study investigates how the subjective experience of one’s interoceptive capacities (called interoceptive awareness) is associated with self-reported orgasm frequency and satisfaction in people who identify as women. Methods: In a dataset of 318 women, orgasm frequency and satisfaction were both rated significantly higher for solitary as compared to partnered sexual experiences. Results: Analysis of how dimensions of interoceptive awareness correlated with orgasm frequency and satisfaction showed that (1) ‘Noticing’ predicted orgasm frequency (but not satisfaction) across both solitary and partnered interactions, (2) ‘Attention Regulation’ predicted greater frequency and satisfaction of solitary orgasm (but not partnered interactions), and (3) ‘Body Trusting’ predicted orgasm satisfaction (but not frequency) across both solitary and partnered contexts. Conclusions: Findings underscore the importance of moving beyond orgasmic dysfunction research by investigating how interoception is associated with healthy—and potentially even optimal—orgasmic functioning in women.